2004
DOI: 10.1128/aem.70.4.1913-1922.2004
|View full text |Cite
|
Sign up to set email alerts
|

Exposure ofSaccharomyces cerevisiaeto Acetaldehyde Induces Sulfur Amino Acid Metabolism and Polyamine Transporter Genes, Which Depend on Met4p and Haa1p Transcription Factors, Respectively

Abstract: Acetaldehyde is a toxic compound produced by Saccharomyces cerevisiae cells under several growth conditions. The adverse effects of this molecule are important, as significant amounts accumulate inside the cells. By means of global gene expression analyses, we have detected the effects of acetaldehyde addition in the expression of about 400 genes. Repressed genes include many genes involved in cell cycle control, cell polarity, and the mitochondrial protein biosynthesis machinery. Increased expression is displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 45 publications
5
70
0
Order By: Relevance
“…Although the changes in expression were slightly different from those found by microarray analysis, expression of both genes were in- 15) . A previous study showed that the sulfur metabolism pathway in S. cerevisiae is induced by acetaldehyde 16) . Acetaldehyde is produced during ethanol fermentation, so furfural might inhibit ethanol production by promoting the accumulation of intermediate compounds, such as acetaldehyde and glycerol 17) .…”
Section: Resultsmentioning
confidence: 99%
“…Although the changes in expression were slightly different from those found by microarray analysis, expression of both genes were in- 15) . A previous study showed that the sulfur metabolism pathway in S. cerevisiae is induced by acetaldehyde 16) . Acetaldehyde is produced during ethanol fermentation, so furfural might inhibit ethanol production by promoting the accumulation of intermediate compounds, such as acetaldehyde and glycerol 17) .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies focusing on wine yeasts have observed transcriptional control of the gene by a sulphur source (Aranda et al, 2006): methionine seems to repress SSU1, especially in the presence of sulphite. Moreover, since sulphite is an intermediate of the superpathway of sulfur amino acid biosynthesis, the expression of genes involved in this pathway (such as some MET genes) has been shown to be related with sulphite detoxification and acetaldehyde production (Aranda & del Olmo, 2004;Aranda et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This analysis revealed an uncharacterized ORF, YLL055w, encoding a putative transporter that was specifically upregulated under sulfur-limiting conditions under both aerobiosis and anaerobiosis, similarly to other sulfur assimilatory enzymes (Boer et al 2003;Tai et al 2005). In addition, this ORF was also found to be induced in a gsh1D strain background (Wheeler et al 2003) (which has reduced intracellular levels of glutathione) and upon exposure to cadmium (Vido et al 2001;Fauchon et al 2002) or acetaldehyde (Aranda and del Olmo 2004), conditions under which most of the genes in the sulfur assimilation pathway were upregulated.…”
Section: Resultsmentioning
confidence: 96%
“…YCT1 is under sulfur regulation and is the major cysteine transporter under sulfur-derepressed conditions: As mentioned earlier, genomewide expression profiling studies have revealed that YCT1 is expressed under conditions of sulfur limitation, cadmium toxicity, lowglutathione levels, and acetaldehyde exposure, conditions under which the entire sulfur assimilation pathway has been shown to be upregulated (Vido et al 2001;Fauchon et al 2002;Boer et al 2003;Wheeler et al 2003;Aranda and del Olmo 2004;Tai et al 2005). To gain further insights into the physiological role of Yct1p, we decided to undertake a more detailed study on the expression pattern of YCT1 in response to different sulfur sources.…”
mentioning
confidence: 95%
See 1 more Smart Citation